(untitled) (Agroindustria, Sociedad y Ambiente, 2025)
ABSTRACT The objective was to evaluate salinity in order to plan the agricultural use of soils; the indicators used were pH, electrical conductivity (EC), and percentage of exchangeable sodium (PSI). A total of 385 soil samples were collected in the municipality of Falcón, Paraguana Peninsula. The spatial distribution of the variables was established using a geographic information system (GIS), which allowed the elaboration of 1: 25,000 scale maps in order to establish the magnitude of the salinity problem in the study area. The soils with alkalinity problems are represented by an area of 899.35 km2 (51% of the territory). The municipality has an area of 324.21 km2 with non-saline soils, slightly saline soils with 949.85 km2, saline soils with 475.64 km2, and strongly saline soils with 14.26 km2 of the territory. The areas with sodicity problems represent 5.5% of the municipality’s surface, and are strongly associated with soils under agricultural use under irrigation with poor quality water. The analysis carried out on the potential of the soils for the establishment of traditional crops showed that maize and sorghum are the crops with the highest potential due to their medium tolerance to the salts. The cultivation of melon presents a potential area for its cultivation of 25% of the surface of the municipality. However, some factors related to management should be considered in order to avoid problems of chemical degradation associated to this type of land use.